Prefiguring Housing Quality in Urban Communities in Ibadan Nigeria - Olusola Oladapo Makinde (SIASAT, 2020)
This study focuses on explaining and understanding the physical factors which reinforced housing quality in urban communities in Ibadan Nigeria. It explained the different physical variables which prefigure housing quality. The study used a conceptual model which recognised nineteen building components consisting of special design features, safety features, building types, buildings orientation, buildings ages, wastes disposal methods and building forms among others. For the questionnaire survey, 985 (20%) respondents out of a total of 4,922 respondents in five randomly selected urban communities in Ibadan were systematically sampled. The information obtained from the survey revealed residents levels of perception of housing quality with their urban communities, which were analysed using Correlation and Relative Important Index. The significant levels of association were determined at either 0.05 or 0.01 probability levels. The results showed significant pearson’s correlation (r) among pairs of the twenty (20) identified relevant housing variables. The results suggested that these factors are stronger determinant of residents’ perception of housing quality. Consequently, closer consideration should be paid to this factor in the design and development of not only existing urban communities but also in the conceptualisation of new ones.